TRMM SATELLITE PERFORMANCE IN ESTIMATED RAINFALL OVER THE MIDWEST REGION OF BRAZIL - Danelichen, Victor Hugo de Morais; Machado, Nadja Gomes; Biudes, Marcelo Sacardi; Souza, Maísa Caldas (Revista Brasileira de Climatologia, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Rainfall is the key element in regional water balance, and have direct influence over economic activity. In this study, we evaluate the estimates of precipitation by TRMM satellite (Tropical Rainfall Measuring Mission) on the Midwest region of Brazil. The rainfall measured by TRMM satellite was compared with rainfall series obtained by the Office of Instituto de Controle de Espaço Aéreo (ICEA) of Comando da Força Aérea. The TRMM satellite overestimated annual rainfall between 0.6 and 37.4%, with greater overestimation in the dry season. However, the rainfall estimate by TRMM satellite had a high correlation (0.88) with the rainfall series and had high Willmott coefficient. The Northern of Brazilian Midwest had the highest annual accumulated rainfall and the Southwest and Northeast of Midwest had the lowest annual accumulated rainfall. There was a inverse seasonal pattern of accumulated rainfall, with higher values in the Northern of Midwest during the rainy season in the Southwest and Northeast during the dry season.